Social engineers and myth-busters: A comparative research on Lithuanian, Norwegian and Serbian language experts - Vukotić, Vuk (Taikomoji kalbotyra, 2019)
This article compares the language ideologies of language experts (both academic and non-academic) in online news media in Lithuania, Norway and Serbia. The results will reveal that language is understood in diametrically opposed ways amongst Lithuanian and Serbian academic experts on the one, and Norwegian academic experts on the other hand. Lithuanian and Serbian academic experts are influenced by modernist ideas of language as a single, homogenous entity, whose borders ideally match the borders of an ethnic group. Norwegian academic experts function in the public sphere as those who try to deconstruct the modernist notion of language by employing an understanding of language as a cognitive tool that performs communicative and other functions. On the other hand, non-academic experts in all the three countries exhibit a striking similarity in their language ideologies, as the great majority expresses modernist ideals of language.